Sheehans syndrome: the hidden nemesis - Ghosh, Labani M.; Leuva, Alpa (International Journal of Research in Medical Sciences, 2020)
Sheehan’s syndrome is the name given to postpartum hypopituitarism, usually precipitated by massive uterine haemorrhage and hypovolemic shock during or after childbirth resulting into pituitary injury in varying degrees. Most cases are diagnosed very late in life and the first presentation may be a life-threatening situation like shock or cardiorespiratory collape. This hidden nemesis in women compromises their quality of life and may result into mortality if not suspected early. In this article we present 3 patients who presented in the ICU in a state of complete cardio-respiratory collapse and later discharged in full health.